STUDI PENDAHULUAN PEMANFAATAN LIMBAH DESALINASI UNTUK PEMBUATAN Mg/Al HYDROTALCITE-LIKE SEBAGAI ADSORBEN METHYL ORANGE - Eddy Heraldy; Dian Prasasti; Karna Wijaya; Sri Juari Santosa; Triyono Triyono (Environmental Research Center (PPLH) of Udayana University, 2012)
The utilization of industrial wastewater into a versatile material that has been the focus of research for economics reasons, environmental and technical. One of the proposed industrial wastewater for a new useful material is wastewater from the desalination process which is also known as brine water. The magnesium content in brine water is able to used as a source of magnesium for the synthesis of Mg/Al hydrotalcite-like compound (Mg/Al HTlc). Mg/Al HTlc are widely investigated for their potential applications in research and industrial processes as adsorbents, catalysts and /or catalyst precursors and pharmaceutical industry excipients. As adsorbents, Mg/Al HTlc are receiving greater interests in the environmental community due to their high adsorption capacity. However, before using natural brine water, has conducted a preliminary study the synthesis of Mg/Al HTlc by using artificial brine water as a model of desalination wastewater. The objective of this research is to synthesis of Mg/Al HTlc from artificial brine water and its ability tested as a methyl orange (MO) adsorbents. The research initiated with the synthesis of Mg/Al HTlc from artificial brine water. Characterization of the Mg/Al HTlc synthesized was confirmed through X-ray Diffraction and FT-IR Spectroscopy. The determination of optimum acidity, adsorption rate, and energy and capacity adsorption were studied. The result showed that pH 3 was the optimum acidity for the adsorption of MO on Mg/Al HTlc. MO was adsorbed at first order adsorption rate of 7.30 × 10-4 s-1 on the Mg/Al HTlc, the adsorption capacity and adsorption energy were 4.36 × 10-5 mol g-1 and 27.54 kJ mol-1, respectively. From the preparatory process and the synthesis of Mg/Al HTlc by using artificial brine water to provide the information that the byproduct of desalination processes (brine water) which are believed to be used for the synthesis of Mg / Al HTlc.